2019
DOI: 10.1186/s12889-018-6299-3
|View full text |Cite
|
Sign up to set email alerts
|

A cholera outbreak in a rural north central Nigerian community: an unmatched case-control study

Abstract: BackgroundCholera remains a disease of public health importance in Nigeria associated with high morbidity and mortality. In November 2014, the Nigeria Field Epidemiology and Laboratory Training Programme (NFELTP) was notified of an increase in suspected cholera cases in Gomani, Kwali Local Government Area. NFELTP residents were deployed to investigate the outbreak with the objectives of verifying the diagnosis, identifying risk factors and instituting appropriate control measures to control the outbreak.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…Olarenwaju (27) reported that in the study of cholera he carried out in Ile-Ife Nigeria, hot spots clusters of cholera cases were seen mainly in areas of very high to high population densities. In the same vein, Dan-Nwafor et al (16) reported that in a study on cholera carried out in Kwali (FCT, North-central part of Nigeria), cholera infections was termed "disease of poverty" because of its association with overcrowded and unclean environmental condition. This was also observed in Durumi community.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Olarenwaju (27) reported that in the study of cholera he carried out in Ile-Ife Nigeria, hot spots clusters of cholera cases were seen mainly in areas of very high to high population densities. In the same vein, Dan-Nwafor et al (16) reported that in a study on cholera carried out in Kwali (FCT, North-central part of Nigeria), cholera infections was termed "disease of poverty" because of its association with overcrowded and unclean environmental condition. This was also observed in Durumi community.…”
Section: Resultsmentioning
confidence: 99%
“…This was also observed in Durumi community. Dan-Nwafor et al (16) had also pointed out the need to apply caution by utilizing the "non-touch technique" in the burial practices there is no significant difference in the mean knowledge of preventive measures score between the different age groups is rejected. This shows that there is significant difference in the mean knowledge of preventive measures score between the different age groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, an estimated 3 -5 million cholera cases and 28,000 -150,000 deaths occur yearly (7,8). Recent estimations also fall within this range with Cholera killing an estimated 95, 000 persons per year and sickening more than 2.86 million people annually (9).…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 1.4 to 4.0 million cases of cholera were reported between 2008¬2012, in 69 cholera-endemic nations [3]. This infection leaves about 21,000 to 143,000 people dead each year [3][4][5][6][7][8]. This estimate is contrasted by Chioma et al [9], who stated that in 2019, the globally estimated number of cholera cases range from 3 to 5 million with 28,000 to 150,000 deaths yearly.…”
Section: Introductionmentioning
confidence: 99%